Med telesom in razumom - Rihtaršič, Urška (Muzikološki zbornik, 2017)
There are three ideal types (Max Weber) of a western classical music performer. These types describe the performer's relationship to composer, musical work and audience. The romantic virtuoso uses music as a means to impress audiences with his personality and corporeality. On the contrary, personality and corporeality of the modernist virtuoso must remain hidden in order to highlight the musical work (Lydia Goehr), which is the result of the composer's intellectual work. In accordance with the general features of postmodern era, the postmodern virtuoso combines and mixes characteristics of previously existing types (pasticcio, palimpsest). This type is also highly defined by the incorporation of postmodern art into the system of late capitalism and the postmodern loss of the specificity of aesthetic experience (Fredric Jameson).
Keywords: modernistični virtuoz; postmodernistični virtuoz; romantični virtuoz